Accidental partial hanging by door curtain causing ischemic encephalopathy in a child: a rare case report - Prasad, Arun; Tiwari, Lokesh; Kumar, Pradeep; Yankappa, N. (International Journal of Contemporary Pediatrics, 2020)
Accidental strangulation is an uncommon injury in children, however it may lead to neurological disability or death. Various modes of injuries have been reported in such accidents. Children might get strangulated while playing if they are wrapping any cord or cloth like material around their neck. Caregivers of the children should be aware of the potential sources around and mechanisms of such injuries to avoid such accidents.